A Paradigm shift in the concept for making dental impressions - Sanjna Nayar; R Mahadevan (Wolters Kluwer Medknow Publications, 2015)
Digital dental impression is a revolutionary technological advancement that so surpasses the accuracy and efficiency of former techniques for obtaining replicas of prepared teeth for the purpose of fabricating restorations that its adoption by dentists is rapidly eclipsing the use of elastomeric impression materials. The ultimate goals of dentists dedicated to quality restorative dentistry are to make their treatment of patients as accurate, stressless, and efficient as possible. By elimination of the everyday problems described above, there is no question that the significant advantages of digital impressions will make intraoral digital scanning standard procedure in most dental offices within the next several years. Furthermore, digital impressions have proven to reduce remakes and returns, as well as increase overall efficiency. The patient also benefits by being provided a far more positive experience. Finally, through the use of digital impression making, it has been determined that laboratory products become more consistent and require less chair time at insertion.